Analysis of brand valuation based on a combination of valuation models - Terzić, Svetlana; Đalić, Irena (Anali Ekonomskog fakulteta u Subotici, 2020)
Branding of companies and products are comparative advantages that can provide growth and development of the company. Estimating the brand in companies is necessary for the purpose of analyzing and determining whether planned investments in the brand will provide the company with adequate wages. In order to achieve this goal, marketing managers need to get to know the value of the brand and the methodology of valuation. By analyzing domestic business practice, it was established that marketing managers do not have enough knowledge about the problem of brand values and methodology of valuation. The aim of the research is to analyze and understand the methodology of valuating the brand based on the combined methods of valuing, in discounting cash flows and royalties. This would indicate the need for more active access to the branding and investment strategy in order to satisfy the interests of companies and consumers.